Antibiotic treatment and prophylaxis of periprosthetic infections: Evaluation of 666 consecutive breast implant removals. Issue 7 (July 2021) - Lohmeyer, J.A.; Jakob, V.L.; Keck, M.; Wittig, K.
Summary: Periprosthetic infections are feared complications in esthetic and reconstructive breast surgery. The purpose of our study is to evaluate our institution's specific culture data and to identify most common organisms and suitable antibiotics for prophylaxis and first-line treatment. We evaluated all patients with a change or removal of breast implants from 01.01.2012 to 31.12.2017 retrospectively. Based on the medical records, the surgical indications were identified and specifically analyzed for signs of infection, reasons for primary and secondary surgery, and all available microbiological data of these interventions. A total of 666 implant removals or exchanges were performed in 431 patients. Microbiological smears were gathered from 291 patients (449 implants). Bacteria were cultured from 63 implants (56 patients). In six additional patients (ten implants), a periprosthetic infection was seen, without bacteria detection. Advanced capsular contracture correlated with a higher proportion of positive swabs ( p <0.05). In 11.5% of smears, bacterial contamination was found despite absence of clinical signs of infection. Coagulase-negative staphylococci were the dominant pathogen in clinical inapparent infections, while Staphylococcus aureus was when there was clinical evidence of infection. All pathogens were sensitive to vancomycin. In the majority of cases, bacterial contamination was an incidental finding, which was more common in the presence of advanced capsular contracture. In our institution, cefuroxime and amoxicillin/clavulanic acid have been proven to be reasonable choices for prevention and treatment of periprosthetic infections. In the treatment of fulminant infections and for the prophylaxis during implant replacement due to advanced capsular contracture, vancomycin became our first choice.